English: Bahasa Indonesia - Lestari, Maya Dwi; Winarno, Sri Tjondro; Atasa, Dita (International Journal of Multidisciplinary Research and Literature, 2023)
Ledug Coffee Indonesia is a trading business engaged in coffee production upstream, downstream, and education. With the large number of similar robusta coffee business actors and the high demand for coffee, Ledug Coffee Indonesia still needs to innovate in diversifying processed coffee to increase added Value and sales through a targeted marketing mix. The purpose of this research is to find out about the amount of said Value of robusta coffee from green bean to roasted bean and from roasted bean to ground coffee and to determine the effect of the marketing mix (7P) of robusta coffee business on consumer buying interest in Ledug Coffee Indonesia methods in research analysis tools Hayami Method and WarpPLS 7.0 with 65 respondents. The results showed that the ratio of added Value generated from processing green beans into roasted beans was 38%, indicating that the Value was considered moderate. The percentage of added Value generated from processing roasted beans into ground coffee is 40%, which suggests that the Value is classified as medium. The results of the analysis of the effect of the 7P marketing mix on consumer buying interest in the robusta variant Ledug Coffee at Ledug Coffee Indonesia, which has a positive and significant impact, namely the product variable (X1), price (X2), people (X5), and process (X6). In contrast, the place variable (X3) has a negative and significant effect. The promotion variable (X4) has a negative and insignificant impact, while the physical evidence variable (X7) has a positive and little influence